Working conditions of medical staff and psychosocial burden during the SARS-CoV-2 pandemic on the example of a selected hospital - Tomaszewska, Katarzyna; Lasota, Paulina (Journal of Education, Health and Sport, 2023)
Nursing staff is a professional group with a high risk of developing health-related disorders. Depression, anxiety and insomnia are the most common symptoms reported by healthcare professionals during the COVID-19 pandemic. Many of these factors lead to a decrease in the quality of life, lower professional performance, cognitive abilities and increase the risk of various diseases among medical staff. The aim of the study was to determine the relationship between selected aspects of the work environment and the health of nurses. Material and methods The study was conducted among 115 nurses employed in a hospital in the Podkarpackie Province. The study used the diagnostic survey method with the use of the interview technique. The research tool was the author's questionnaire. Results The study shows that the group of nurses did not differ from each other in terms of difficulties in concentrating and making decisions, as well as experiencing fear and anxiety while working with a patient with COVID-19. This may be related to getting used to the specificity of work, the intensity and frequency of long-term patient care. Work in the Temporary Covid Ward was not significantly related to lower mental health ratings, worse sleep quality or insomnia, which was indicated as a rare phenomenon (36.5%). The respondents pointed to a shortage of medical personnel (87.8%) and work in PPE (86.1%). Conclusions The pandemic had an impact on the health of nurses and male nurses during the pandemic. The most common health effects among nurses were dermatological problems caused by disinfection detergents, less often they were problems related to the urinary system. Nurses have knowledge in the field of prevention and taking care of their own health while working in a pandemic. Socio-demographic factors had an impact on the health status of nurses.